High-fidelity physics based models (HFPBM) for FRP-strengthened RC walls subject to near-field blast effects and fragment loading - Fung, Tat Ching (Nanyang Technological University, 2020)
In this report D3, the aim is to develop a high-fidelity physics based models (HFPBM) by commercial hydro code LS-DYNA for FRP-strengthened RC walls subject to near-field blast effects and fragment loading. The models should be validated using the DSTA test results or other available test results. Based on the work from report D1, D2 and also some other previous projects by our group, in this report D3, the involved techniques of numerical simulation will be investigated one by one. Finally high-fidelity physics based models (HFPBM) will be developed.